Self in the Last Essays of Elia - Dr.Atul Kumar Kanojia (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2019)
Self in the last essay of Elia Lamb's last essays tells a lot about small details, the great agonies his first impression the play of a mind and the play on words. The main point of this paper to study the difference between the letter writing who signed himself C.L. and the essayist known as Elia. So, Lamb was having a charming and captivating personality. He used to say about himself that he loves reading, walking and writing. Lamb lived as a social Hero who was never defeated by the challenges of life.